The aeration of clay soils in cricket - Parsons, Simon A. (Cranfield University, 2012)
In the game of cricket good ball-surface interactions are essential and require a hard, flat surface. To achieve this the clay loam soil comprising the pitch is compressed and compacted using a smooth wheeled roller, which when combined with the drying action of the grass plant roots, causing the clay minerals within the soil to shrink, creates a high bulk density, hard surface on which to play. High bulk density soils present difficult growing conditions for plants due to high mechanical resistance, reduced hydraulic conductivity and gas exchange capability. The hydraulic properties and gas exchange capability are linked to the connectivity and tortuosity of the pore network as well as pore size; all of which are diminished by compaction of the soil. Aeration is currently utilised as a tool to ameliorate the negative effects of compaction on the growing environment of the plant roots. Little research exists that describes the actions of aeration in clay loam soils. The current guidelines for aeration and the proof for its efficacy in cricket are based almost entirely on anecdotal evidence. A diverse methodology was used to meet the project objectives. This diversity reflects the broad nature of the expectations of the cricket groundsmen from aeration of pitches as reflected in a survey of current practise undertaken during the project. Novel experimental methods were used to examine the effect of aeration on soil atmospheres in the laboratory and under field conditions. The laboratory experiment revealed that vertically-operated solid tines did significantly increase the rate of diffusion through the soil, however in the field, this rate increase was only apparent after significant rainfall. New methods utilising time-lapse photography and automated image analysis quantified the magnitude of swelling in a range of soils in response to increasing water content over time to a high degree of accuracy. A similar method was employed to examine the shrinkage of the same soils as the water content was reduced, examining not only the magnitude but also the cracking patterns formed. These experiments aimed to examine the soils natural ability to recover from compaction over time. The soils natural ability to recover from compaction through shrink-swell and freeze-thaw was evident in the field trials. These field trials examined five diverse aeration treatments to examine the physical and biological effects they have on the soil. The field trials showed generally small and inconsistent effects on the physical properties of the soil from aeration treatments when compared to the natural processes of shrink-swell and freeze-thaw. One consistent effect from aeration was a 2% reduction in moisture content in one particular soil type. Aeration was found to have no effect on soil microbial biomass nor on soil organic matter content. In a pot experiment examining the effect of aeration in a range of soil densities the total root mass was not diminished by increasing soil density but became increasingly concentrated upwards in the profile. Aeration was found to slightly increase the root mass but only in the highest bulk density treatment (1.90 g cm-3) at depths below 75 mm. A set of guidelines were developed based on the evidence garnered from the experiments with a clearly defined decision process for choosing the most suitable equipment for the treatment aim. It is hoped that these guidelines will provide an informative reference for current and future groundsmen to ensure the optimum use of often scarce and valuable resources when choosing an aeration treatment.